Analysis of The Influence of the Social Environment on Vocabulary Mastery in Children - Susiani, Susiani; Fitri Rizki, Fitri Rizki; Rizky Khairunnisa Sormin (Jurnal Manajemen, Pendidikan Dan Ilmu Komputer, 2025)
Vocabulary mastery in children is a key aspect in language development, which is influenced by the social environment. This material analyzes the influence offamily, peers, and the formal education environment on children’s vocabulary mastery through case examples and effective strategies. The role of the family in forming children’s language foundations, positive interactions with peers, and implementing vocabulary-based project in formal education environments in the main focus. Effective strategies, such as vocabulary-based family activities, promoting social interaction, and collaboration with the educational environment, are emphasized to improve children’s vocabulary mastery. The conclusion emphasizes to importance of understanding and implementing these factors in creating an environment that supports children’s language development.